The emerging modulators of non-coding RNAs in diabetic wound healing - Aghayants, Sis; Zhu, Jinjin; Yu, Jing; Tao, Rui; Li, Sicheng; Zhou, Shengzhi; Zhou, Yunhua; Zhu, Zhanyong (Frontiers in Endocrinology, 2024)
Diabetic wound healing is a complex physiological process often hindered by the underlying metabolic dysfunctions associated with diabetes. Despite existing treatments, there remains a critical need to explore innovative therapeutic strategies to improve patient outcomes. This article comprehensively examines the roles of non-coding RNAs (ncRNAs), specifically microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), in regulating key phases of the wound healing process: inflammation, angiogenesis, re-epithelialization, and tissue remodeling. Through a deep review of current literature, we discuss recent discoveries of ncRNAs that have been shown to either promote or impair the wound healing process in diabetic wound healing, which were not covered in earlier reviews. This review highlights the specific mechanisms by which these ncRNAs impact cellular behaviors and pathways critical to each healing stage. Our findings indicate that understanding these recently identified ncRNAs provides new insights into their potential roles in diabetic wound healing, thereby contributing valuable knowledge for future research directions in this field.